تأثير تدريبات المقاومات المتغيرة على التوازن الديناميكي ومهارات الرجلين لدى لاعبي منتخب مصر للكوميتيه - البشيهي، محمود ربيع أمين (جامعة حلوان - كلية التربية الرياضية للبنات, 2020)
مقدمة: تتميز مهارات الكاراتيه بالسرعة العالية في أدائها، كما تتطلب درجة عالية من التوازن وتحريك أكثر من جزء من أجزاء الجسم في أن واحد مع قاعدة ارتكاز صغيرة جدا أثناء أداء بعض المهارات، وأيضا تتطلب درجة معينة من القوة والرشاقة. وتعتبر رياضة الكاراتيه إحدى رياضات الدفاع عن النفس والتي تؤدى من خلال مجموعة من اللكمات والركلات. الهدف: يهدف البحث الحالي إلى التعرف على تأثير استخدام مجموعة من تدريبات المقاومات المتغيرة على تحسين مستوى التوازن الديناميكي ومستوى أداء بعض مهارات الرجلين للاعبي منتخب مصر للكوميتيه. الإجراءات: تكونت عينة البحث من (15) خمسة عشر لاعب من لاعبي منتخب مصر للكوميتيه فوق (18) سنة. تم تحليل البيانات باستخدام البرنامج الإحصائي SPSS (الإصدار 22). النتائج: تؤكد نتائج البحث أن تدريبات المقاومات المتغيرة قد أثرت تأثيرا إيجابيا على مستوى التوازن الديناميكي الخاص بلاعبي منتخب مصر للكوميتيه (عينة البحث) بنسب تتراوح بين (13 %، 21 %). كما أثرت مجموعة تدريبات المقاومات المتغيرة تأثير إيجابيا على مستوى أداء مجموعة مهارات الرجلين (قيد البحث) لدى لاعبي منتخب مصر للكوميتيه (عينة البحث) حيث ساهمت في تحسين مستوى أداء تلك المهارات بنسب تراوحت بين (12 %، 20 %). المناقشة: اتفاقا مع مجموعة من الدراسات الأخرى تؤكد الدراسة الحالية نجاح مجموعة تدريبات المقاومات المتغيرة التي تم وضعها في الارتقاء بمستوى التوازن الديناميكي ومستوى مهارات الرجلين (قيد البحث) لدى عينة البحث من لاعبي منتخب مصر للكوميتيه. Introduction Karate skills are characterized by high speed in their performance, as well as require a high degree of balance and move more than one part of the body at the same time with a very small fulcrum while performing some skills, and also require a certain degree of strength and agility. Karate is a self-defense sport that is performed through a combination of punches and kicks. Aim The current research aims to identify the effect of using a set of variable resistance exercises on improving the level of dynamic balance and the level of performance of some of legs skills for the Egyptian kumite team players. Method The research sample consisted of (15) fifteen players from the Egyptian Kumite national team over (18) years old. Data were analyzed using SPSS statistical software (version 22). Results The results of the research confirm that the variable resistance training had a positive effect on the dynamic balance level of the Egyptian Kumite players (the research sample), with rates ranging between (13% and 21%). The group of variable resistance training also had a positive effect on the performance level of the legs skills group (under investigation) among the Egyptian kumite players (the research sample), as it contributed to improving the performance of those skills at rates ranging between (12% and 20%). Discussion In agreement with a group of other studies, the current study confirms the success of the variable resistance training group that was developed in upgrading the level of dynamic balance and the level of legs skills (under investigation) of the research sample of the Egyptian kumite players.
Keywords: التوازن الديناميكي -- رياضة الكاراتيه -- التربية البدنية -- التدريب الرياضي